The Human-Centered Design With Iterative Service-Learning Framework: Applied to Small Rural Organizations - Weitl-Harms, Sherri (Journal of Organizational Psychology, 2025)
The innovative framework described in this work integrates human-centered design principles with iterative service-learning to incrementally develop and improve computing artifacts. An application is demonstrated through work with small rural organizations, who rarely have the expertise or resources to develop computing artifacts to market and deliver their products and services. Historically, service-learning team projects once delivered are not updated. Additionally, there are few structured guides for assisting the implementation of service-learning. Human-centered design has been shown to improve the quality of computing artifacts. Yet, even when using human-centered design principles, computing artifacts rarely function well long-term without updates. The proposed framework addresses issues plaguing service-learning's success while developing high-quality artifacts. A step-by-step execution guide is provided, along with a sample longitudinal application. The framework was qualitatively and quantitatively evaluated at multiple points in the implementation. This research also analyzed impact and found both students and clients reporting high satisfaction levels.